2006
DOI: 10.1111/j.1471-4159.2006.04156.x
|View full text |Cite
|
Sign up to set email alerts
|

Electroconvulsive seizure‐induced gene expression profile of the hippocampus dentate gyrus granule cell layer

Abstract: Electroconvulsive shock (ECS) is the most effective treatment for depression, but the mechanism underlying the therapeutic action of this treatment is still unknown. To better understand the molecular changes that may be necessary for the clinical effectiveness of ECS we have combined the technologies of gene expression profiling using cDNA microarrays with T7-based RNA amplification and laser microdissection to identify regulated genes in the dentate gyrus granule cell layer of the hippocampus. We have identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 75 publications
(106 reference statements)
1
67
0
1
Order By: Relevance
“…The fact that 5-HT does not regulate expression of all BDNF-induced genes suggests that BDNF is involved in numerous cellular processes, whereas 5-HT may have a more defined role in the hippocampus. The common set of specific genes we identified as regulated by both 5-HT and BDNF relate to neuronal activation, synaptic remodeling, and neuropeptides, and parallels those classes of genes altered by various antidepressant treatments (Newton et al, 2003;Altar et al, 2004;Alfonso et al, 2005;Yamada and Higuchi, 2005;Ploski et al, 2006;Conti et al, 2007).…”
Section: Discussionmentioning
confidence: 62%
“…The fact that 5-HT does not regulate expression of all BDNF-induced genes suggests that BDNF is involved in numerous cellular processes, whereas 5-HT may have a more defined role in the hippocampus. The common set of specific genes we identified as regulated by both 5-HT and BDNF relate to neuronal activation, synaptic remodeling, and neuropeptides, and parallels those classes of genes altered by various antidepressant treatments (Newton et al, 2003;Altar et al, 2004;Alfonso et al, 2005;Yamada and Higuchi, 2005;Ploski et al, 2006;Conti et al, 2007).…”
Section: Discussionmentioning
confidence: 62%
“…There is also growing evidence that antidepressant treatments may exert some of their therapeutic effects by increasing BDNF expression levels and affecting BDNF transcription in the hippocampus. Thus, (i) electroconvulsive brain stimulation, a treatment of choice for medication‐resistant depression, increases the hippocampal contents of BDNF and trkB mRNAs (Altar, Whitehead, Chen, Wörtwein, & Madsen, 2003; Angelucci, Aloe, Jiménez‐Vasquez, & Mathé, 2002; Nibuya et al., 1995), particularly in the dorsal hippocampus (Ploski et al., 2006), (ii) antidepressant treatment rapidly elevates the content of BDNF mature protein via posttranscriptional mechanisms, prevents the stress‐induced decrease in the hippocampal concentration of BDNF mRNA and counteracts the depression‐associated alterations in neural plasticity by normalizing BDNF in the rodent prefrontal cortex and hippocampus (Baj et al., 2012; Kozisek et al., 2008; Musazzi et al., 2009). In keeping with these experimental findings, postmortem samples from clinically depressed patients treated with antidepressant medications show increased BDNF immunoreactivity in the hilus, the dentate gyrus and the supragranular regions of the hippocampus as compared with antidepressant‐untreated controls (Chen, Dowlatshahi, MacQueen, Wang, & Young, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies have shown that, in rats, the bilateral infusion of BDNF into the dentate gyrus of the dorsal hippocampus produces antidepressant‐like effects in behavioral depression models (Shirayama, Chen, Nakagawa, Russell, & Duman, 2002); moreover, in the dorsal hippocampus, chronic electroconvulsive treatment increases the acute electroconvulsive induction and prolongs the expression of BDNF and trkB mRNA (Nibuya et al., 1995), and also up‐regulates the expression of the gene encoding BDNF in the dentate gyrus granule cell layer (Ploski, Newton, & Duman, 2006). Hence, the present study was designed to characterize the hippocampal distribution of BDNF and its receptor trkB in RHA and RLA rats under baseline conditions, with special focus on the dorsal hippocampus, using Western blot (WB) and immunohistochemistry techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative real-time PCR (qRT-PCR) was performed using the ⌬⌬Ct method as described previously (Ploski et al, 2006) using qRT-PCR primers for Arc/Arg3.1 (forward primer CCCTGCAGCCCAAGT-TCAAG; reverse primer GAAGGCTCAGCTGCCTGCTC). Relative gene concentrations were normalized against GAPDH (forward primer GCATCCTGCACCACCAACTG; reverse primer ACGCCACAGCTT-TCCAGAGG).…”
Section: Methodsmentioning
confidence: 99%